2016
DOI: 10.1111/iwj.12692
|View full text |Cite
|
Sign up to set email alerts
|

Poor methodological quality and reporting standards of systematic reviews in burn care management

Abstract: The methodological and reporting quality of burn-specific systematic reviews has not been established. The aim of this study was to evaluate the methodological quality of systematic reviews in burn care management. Computerised searches were performed in Ovid MEDLINE, Ovid EMBASE and The Cochrane Library through to February 2016 for systematic reviews relevant to burn care using medical subject and free-text terms such as 'burn', 'systematic review' or 'meta-analysis'. Additional studies were identified by han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 158 publications
(151 reference statements)
5
28
2
1
Order By: Relevance
“…Some studies have found that author affiliation to the Cochrane Collaboration is a predictor of the methodological quality of SRs and MAs . Although this subgroup of reviews achieved the highest AMSTAR scores in our study, we did not observe Cochrane affiliation as a quality predictor.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Some studies have found that author affiliation to the Cochrane Collaboration is a predictor of the methodological quality of SRs and MAs . Although this subgroup of reviews achieved the highest AMSTAR scores in our study, we did not observe Cochrane affiliation as a quality predictor.…”
Section: Discussioncontrasting
confidence: 92%
“…3 Some studies have found that author affiliation to the Cochrane Collaboration is a predictor of the methodological quality of SRs and MAs. [51][52][53] Although this subgroup of reviews achieved the highest AMSTAR scores in our study, we did not observe Cochrane affiliation as a quality predictor. This may be due to the fact that most of these studies performed a linear regression using the total AMSTAR score as a predicting variable.…”
Section: Discussioncontrasting
confidence: 75%
“…But the quality of the reporting and methodology have been suboptimal. What is more, eligible articles of superior quality need to contain the (Cullis et al, 2017;Shi et al, 2014;Wasiak et al, 2016) have evaluated compliance with the PRISMA statement and AMSTAR tool in other medical disciplines. An assessment of the leading gastroenterology and hepatology journals from 2006 to 2008 and from 2012 to 2014 showed the mean PRISMA and AMSTAR scores were 20.800 and 7.600, respectively (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Reporting guidelines are in place for systematic reviews in the form of the PRISMA statement [ 19 , 20 ] to promote adherence to good practice, but again, uptake of compliance with guidance from systematic review authors is varied [ 7 ] and often poor. Wasiak and colleagues [ 21 ] report that, from a review of 60 systematic reviews in burn care management, 13 of the 27 PRISMA checklist items were addressed in less than 50% of cases. Whilst journals may stipulate to authors that the PRISMA checklist is followed when submitting systematic reviews for publication, peer reviewers and journal editors may be unlikely to find the time to monitor or regulate authors adherence to these guidelines, in addition to reviewing the scientific and reporting quality of the draft manuscript.…”
Section: Main Textmentioning
confidence: 99%